Staying awake: truck drivers’ vulnerability in Rio Grande do Sul, Southern Brazil - Knauth, Daniela Riva; Pilecco, Flávia Bulegon; Leal, Andréa Fachel; Seffner, Fernando; Teixeira, Ana Maria Ferreira Borges (Revista de Saúde Pública, 2012)
OBJECTIVE: To analyze factors associated with the use of stimulants by truck drivers to stay awake. METHODS: A survey with 854 drivers was carried out at eight truck stops (seven gas stations and one border patrol post) located at five cities in the State of Rio Grande do Sul (Southern Brazil) in 2006. The outcome "amphetamine use" was categorized as "yes" or "no". Poisson regression analysis with robust variance was conducted in order to select the variables that would be included in the model, which was composed of variables regarding socioeconomic and demographic characteristics, information on the profession and on alcohol consumption. RESULTS: Amphetamine use to stay awake was reported by 12.4% of the truck drivers, either in isolation or in combination with other substances (coffee, guaraná powder, energy drinks, snorted cocaine). Amphetamine was the most cited substance by those who consumed something to stay awake. The consumption of alcoholic drinks was mentioned by more than 70% of the interviewees; among those who drink, 45.1% reported that they use alcohol at least once a week. Amphetamine use was associated with younger age groups, wage increase, longer trips, and alcohol use. CONCLUSIONS: The increase in the truck drivers' wages implies increased workloads. This produces physical and emotional stress, which makes the truck drivers search for a temporary solution in the consumption of stimulants. The reduction in the abusive consumption of alcohol and in the illicit use of substances like amphetamines by professional drivers depends not only on policies addressing prevention and treatment for drug abuse, but also on integrated policies ensuring better working and health conditions to the truck drivers.